Characteristics of organizational culture and climate in knowledge-intensive organisations - Cristina Leovaridis; Diana Maria Cismaru (Romanian Journal of Communications and Public Relations, 2016)
The article focuses on organizational culture and climate in knowledge-intensive organizations, aiming to identify the specific values and features of climate for each sector.The sample of organizations included organizations from five sectors: higher education, banking and financial, research and development, IT and marketing-advertising. The qualitative design of research included near 80 in-depth interviews with employees and managers. The results showed that climate was based on various characteristics: human relations and friendship in small marketing-advertising agencies and IT companies, competition in large advertising companies. In the research development sector, the climate was based on achieving goals in the private area of the sector ( in higher education as well), while in the public areat of the sector it was based on freedom and creativity. The climate in the banking sector was very different, being based on discipline and obeying rules. From the point of view of the organizational culture, all the interviewed employees of the advertising, IT and banking sector experienced, inside the company, the presence of certain forms of organizational culture. Only half of the interviewees from the higher education sector admit to the presence of an organizational culture in their institution while in the public funded research-development sector, employees reportedly did not experience visible manifestations of any type of organizational culture.S